Конокрад: роман / Михаил Щукин - Щукин Михаил Николаевич (Сибириада, 2022)
Экземпляры: ф.18 (20230410) / Инвентарный номер: 4441 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: Щ 95 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44